Burnout akademik selama pandemi Covid-19 - Karimah Al-Marwaziyyah; Devrita Irenike Mayade Chori (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the experience of the students during online learning. The subjectsconsisted of 10 students who were running online learning with an age range of 18-25 years. The method used is asemi-structured interview with a qualitative phenomenological approach. The results show that the subject quicklyfeels emotional changes (mood swings) during online learning. Sometimes the subjects become more sensitive totheir families at home, when they are tired they express negative emotions by crying, and get angry when there areno ideas when doing the assignments. Some of these things cause individuals to feel pressured with the collegeassignments, so they experience academic burnout.